Effects Of Bio-Oil - Diesel Blends: The Performance and Emissions of Diesel Engines With Heater on Fuel Blends - Farid Majedi; Achmad Aminudin; Indah Puspitasari; Alfi Tranggono Agus Salim; Arfan Ferini Yusri (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
The vehicle fuel consumption is increasing. Fossil fuels are running low. Research is needed to reduce the use of fossil fuels. As an alternative, research is carried out on the use of a mixture of bio-oil - diesel fuel in diesel engines. The aim of the research is to increase power, reduce fuel consumption and reduce exhaust emissions from diesel engines. The research method is direct testing on diesel engines with variations in fuel heating by adding a heater to the fuel. Variation of heating materials The fuel used is standard temperature, 40°C, 50°C, and 60°C. The test uses a lamp load with a certain variation to determine power, with a measuring tube to determine certain fuel consumption. Testing using the opacity smoke meter to determine the level of exhaust gas opacity. In this test, In this test it can be concluded that the best condition is B20 at a fuel heating temperature of 40oC, where power has increased, opacity and fuel consumption has decreased, the power can reach 2592,76 watt. Smoke opacity level at 5,4% and 0,088 gr/watt of fuel consumption.